Rancang Bangun Sistem Kontrol Motor 3 Phase Berbasis Iot - M. Ismail, KGS.; Inten Suwono, Niedya; Maulana, Rizki; Fahrizal, Danis; Setiawan, Singgih; Muliawati, Yuli (Program Studi Teknik Mekanikal Bandar Udara, 2024)
An induction motor, which is particularly useful in the aviation sector, is a motor that runs on alternating current, or AC energy. Because they are highly effective and reasonably priced for the industrial sector, three phase induction motors are commonly employed in this industry. A 3-phase induction motor's inability to maintain a consistent speed in the event of a fast load shift is one of its limitations. Its multiple non-linear characteristic characteristics are another. Therefore, a controller is required to provide a steady speed and improved system performance against variations in load. Three-phase induction motor speed control may be achieved in a number of ways, one of which is through the advancements in control systems brought about by the growing usage of the internet. The Internet of Things, or IoT, is an improvement in technology that allows several electrical items to be remotely managed via the internet, providing a faster and more effective control mechanism